$α$-$(h,e)$-convex operators and applications for Riemann-Liouville fractional differential equations - Zhou, Bibo; Zhang, Lingling (Topological Methods in Nonlinear Analysis, 2023)
In this paper, we consider a class of $α$-$(h,e)$-convex operators defined in set $P_{h,e}$ and applications with $α> 1$. Without assuming the operatorto be completely continuous or compact, by employing cone theory and monotone iterative technique, we not only obtain the existence and uniqueness of fixed pointof $α$-$(h,e)$-convex operators, but also construct two monotone iterative sequences to approximate the unique fixed point. At last, we investigate the existence-uniqueness of a nontrivial solution for Riemann-Liouville fractional differential equations integral boundary value problems by employing$α$-$(h,e)$-convex operators fixed point theorem.